The Effect of Storytelling on Improving Compliance with Clean and Healthy Living Behavior (CHLB) Among School-Aged Children at SD Negeri Batuplat 2 - Bhwa, Daeng Agus Vieya Putri; Toulasik, Anita W; Seran, Alfonsa Ivoni Larys; Laoepada, Juwita Puput Rogi (INDOGENIUS, 2025)
Background & Objective: Clean and Healthy Living Behavior (PHBS) is a crucial component in improving the health of school-age children. This study aims to evaluate the impact of the storytelling method on school-age children's adherence to PHBS. Method: This research utilized a quasi-experimental design with a pretest-posttest control group approach. The study population consisted of 160 fourth and fifth-grade students from SD Negeri Batuplat 2. A total of 80 students were randomly assigned to the intervention and control groups, with 40 students in each group. The intervention involved PHBS-themed storytelling sessions conducted over four weeks. Data were collected using a PHBS adherence observation questionnaire and analyzed using paired t-tests and independent t-tests. Result: The results showed a significant improvement in PHBS adherence in the intervention group compared to the control group (p < 0.05). Conclusion: Storytelling has been proven effective in improving clean and healthy living behavior adherence among elementary school children and can be utilized as a method in health education.